Implementation of Marketing Mix on Purchasing Decisions in the Mixue Comal Drink Industry - Natasya Stifani Harikha; Gunawan Aji; Ilham Ahmad Fahreza; Fina Qoif Fiana (TALENTA Publisher, Universitas Sumatera Utara, 2024)
This research uses a qualitative descriptive approach and collects data through interviews about relevant literature or library materials, such as books, journals and websites, related to the research subject. The beverage industry has grown rapidly in recent years. There is no worry that many investors are interested in investing in Indonesia, and mixue is one of them. The Mixue franchise company was founded in Zhengzhou, Henan Province, China, in June 1997, and sells tea drinks and soft serve ice cream. The marketing mix or marketing mix is a marketing tool that forms a strategy for the company's marketing activities to achieve the company's vision and mission in an optimal way. This writing aims to analyze how the use of Marketing Mix has an impact on the Mixue beverage industry and whether it influences purchasing decisions in this industry. The results of this research show that Mixue Comal uses a Marketing Mix system, which consists of seven marketing components including product, price, place, promotion, people, processes and facilities which have a positive impact on the beverage industry and Mixue Comal purchasing decisions.